2014
DOI: 10.1007/s00408-014-9664-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Characteristics, Histological Features and Clinical Outcomes of Lung Cancer Patients with Coexistent Idiopathic Pulmonary Fibrosis

Abstract: At our centre, 1/20 patients with lung cancer have concomitant IPF. The majority of these tumours are small in size, peripheral in location and squamous cell carcinoma; in an area of honey combing. The outcome for concomitant lung cancer and IPF regardless of stage or therapy is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…Furthermore, Khan et al. have reported a striking transition from metaplastic squamous epithelium (within the fibrotic areas) to invasive carcinoma in 50% of the resected squamous cell tumors from patients with IPF . Based on these findings, it is possible that lung cancer in patients with CPFE has a similar developmental process to that of lung cancer in patients with IPF, as these two groups exhibit increasing epithelial atypia, atypical metaplasia to carcinoma in situ, and invasive carcinoma in the surrounding fibrotic area.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Khan et al. have reported a striking transition from metaplastic squamous epithelium (within the fibrotic areas) to invasive carcinoma in 50% of the resected squamous cell tumors from patients with IPF . Based on these findings, it is possible that lung cancer in patients with CPFE has a similar developmental process to that of lung cancer in patients with IPF, as these two groups exhibit increasing epithelial atypia, atypical metaplasia to carcinoma in situ, and invasive carcinoma in the surrounding fibrotic area.…”
Section: Discussionmentioning
confidence: 98%
“…In a large retrospective analysis, about one in 20 patients presenting with lung cancer had a concomitant IPF, the majority of tumors being squamous cell, small in size, and peripheral in location arising in an area of honeycombing. Th e outcome of therapy for lung cancer was extremely poor regardless of tumor stage or severity of IPF, 10 although other studies demonstrated that surgery can be off ered to properly selected patients with ILD. 11…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Lung cancer in IPF patients generally starts in peripheral areas of lung fibrosis. If fine needle aspiration biopsy (FNAB) can not be performed or is not diagnostic, the management of these patients becomes difficult (16). The international guidelines for the diagnosis and treatment of IPF do not provide a clear strategy on how to manage these patients whose survival is reduced by the presence of the highly suspected or even histologically confirmed lung cancer (1,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…It generally occurs in the peripheral areas of the lower lobes, where fibrotic changes are predominant. In particular, LC develops from honeycomb areas or in the border between honeycombing and non fibrotic areas and the squamous cell carcinoma is the predominant histological type (16,17). Invasive diagnostic or therapeutic procedures for neoplasms promote the development of Acute exacerbations (AE) in 80% of IPF patients and the lung surgical treatment puts about 1/5 of them at high risk of death (17,18).…”
mentioning
confidence: 99%